2015
DOI: 10.1016/j.dci.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum suppresses the host immune response by inducing the synthesis of insulin-like peptides (ILPs) in the mosquito Anopheles stephensi

Abstract: The insulin-like peptides (ILPs) and their respective signaling and regulatory pathways are highly conserved across phyla. In invertebrates, ILPs regulate diverse physiological processes, including metabolism, reproduction, behavior, and immunity. We previously reported that blood feeding alone induced minimal changes in ILP expression in Anopheles stephensi. However, ingestion of a blood meal containing human insulin or Plasmodium falciparum, which can mimic insulin signaling, leads to significant increases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 77 publications
3
36
0
Order By: Relevance
“…Accordingly, we used this concentration of ILPs in our feeding assays. Provision of 170 pM ILP4 significantly increased the prevalence (proportion of mosquitoes infected) of infection (Figure 1A) from 57.8 to 80.8% and the intensity (oocysts/midgut) of infection (Figure 1B) from 1.11 to 2.13 oocysts/midgut when compared with controls, as predicted by our recent work [13]. Surprisingly, feeding of 170 pM ILP3 significantly decreased the prevalence of infection from 62.2 to 54.3% (Figure 1C), but had no effect on the intensity of infection relative to controls (Figure 1D).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Accordingly, we used this concentration of ILPs in our feeding assays. Provision of 170 pM ILP4 significantly increased the prevalence (proportion of mosquitoes infected) of infection (Figure 1A) from 57.8 to 80.8% and the intensity (oocysts/midgut) of infection (Figure 1B) from 1.11 to 2.13 oocysts/midgut when compared with controls, as predicted by our recent work [13]. Surprisingly, feeding of 170 pM ILP3 significantly decreased the prevalence of infection from 62.2 to 54.3% (Figure 1C), but had no effect on the intensity of infection relative to controls (Figure 1D).…”
Section: Resultssupporting
confidence: 85%
“…We have previously shown that knockdown of either ILP3 or ILP4 can significantly reduce the prevalence and intensity of P. falciparum infection in A. stephensi , suggesting that mosquito ILPs are immunosuppressive [13]. While the primary aim of the present study was to determine the mechanisms by which these ILPs modulate resistance to infection, we first sought to extend previous findings by characterizing the phenotypic effects of these peptides using ILP provisioning as a complement to our knockdown studies.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…2). This repression was consistent with ABA’s effect on infection given that knockdown of ILP3 and ILP4 is also associated with reduced P. falciparum infection in A. stephensi [12]. Addition of 100 nM ABA to a P. falciparum -infected blood meal had no effect on phosphorylation of ERK, JNK or p38 MAPK relative to controls (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Data were normalized to transcript levels for A. stephensi ribosomal s7 protein, a18s rDNA, and control levels as previously described [12]. nos , defensin , apl1 , tep1 , and lrim transcript levels were determined by qRT-PCR and analyzed as described previously [1].…”
Section: Methodsmentioning
confidence: 99%